Methodological? Or Dialectical?: Reflections of Scientific Inquiry in Biology Textbooks - DOĞAN, ÖZGÜR KIVILCAN (Springer, 2020)
Given the importance of cultivating scientific literate societies, the integration of scientific inquiry into school curriculum is key to contemporary science education. It is apparent that textbooks have been an accessible source of science information for teachers and students since the growth of public K-12 schooling worldwide. Textbooks are crucial for understanding the basis of science curriculum, since many science teachers design their courses according to textbook content. This study aimed to determine whether the activities (both experiments and student activities) in Turkish biology textbooks reflect contemporary inquiry-based approaches. To this end, the sample of the study was composed of four biology textbooks approved by the Turkish Ministry of National Education (MoNE) for grades 9–12. Analysis of these textbooks was conducted using the Inquiry-Based Tasks Analysis Inventory (ITAI). The overall findings indicate that activities in textbooks were mostly compatible with the established curriculum, but they were insufficiently designed to prepare students to do inquiry or to understand what scientific inquiry is. Results demonstrated that these textbooks’ most considered ITAI dimension was Construction of Understandings about Scientific Concepts, while the least frequently explored dimension was Understandings about Scientific Inquiry. Additionally, in the Expected skills dimension, observing and inferring were the most frequently used skills. © 2020, Ministry of Science and Technology, Taiwan.
Keywords: Biology education; ITAI; Scientific inquiry; Textbooks